2018
DOI: 10.1093/mnras/sty2007
|View full text |Cite|
|
Sign up to set email alerts
|

Testing gravity with wide binary stars like α Centauri

Abstract: We consider the feasibility of testing Newtonian gravity at low accelerations using wide binary (WB) stars separated by 3 kAU. These systems probe the accelerations at which galaxy rotation curves unexpectedly flatline, possibly due to Modified Newtonian Dynamics (MOND). We conduct Newtonian and MOND simulations of WBs covering a grid of model parameters in the system mass, semi-major axis, eccentricity and orbital plane. We self-consistently include the external field (EF) from the rest of the Galaxy on the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(121 citation statements)
references
References 139 publications
(182 reference statements)
3
118
0
Order By: Relevance
“…Radio tracking data from Cassini has placed strong constraints on the MOND interpolating function, though some choices are still consistent with observations (Hees et al 2014(Hees et al , 2016. Nearby wide binary stellar systems could be even more important as the MOND circular velocity exceeds the Newtonian value by ≈ 20% (Banik & Zhao 2018). Such systems do appear to show a departure from Newtonian expectations , though it was later shown that the two can be reconciled with a more careful rejection of outliers (Banik 2019).…”
Section: Comparison With Hernandez (2019)mentioning
confidence: 84%
See 1 more Smart Citation
“…Radio tracking data from Cassini has placed strong constraints on the MOND interpolating function, though some choices are still consistent with observations (Hees et al 2014(Hees et al , 2016. Nearby wide binary stellar systems could be even more important as the MOND circular velocity exceeds the Newtonian value by ≈ 20% (Banik & Zhao 2018). Such systems do appear to show a departure from Newtonian expectations , though it was later shown that the two can be reconciled with a more careful rejection of outliers (Banik 2019).…”
Section: Comparison With Hernandez (2019)mentioning
confidence: 84%
“…For MOND, the dynamics of wide binary stars is a promising 'experimentum crucis' in the near future (e.g. Banik & Zhao 2018). If the observed dynamical discrepancies are due to DM, then massive objects moving through the Galactic DM halo should experience dynamical friction (Chandrasekhar 1943).…”
Section: Introductionmentioning
confidence: 99%
“…If a slightly heavier spacecraft can be launched, it might be possible to perform Cavendish-style gravitational experiments beyond the Sun's MOND radius. As discussed in Banik & Zhao (2018d, figure 1), the force between two point masses would exceed the Newtonian expectation by ≈ 30 − 60% depending on their heliocentric distance, orientation with respect to the Galactic external field and, to a smaller extent, their mass ratio (see their figure 8). In general, the force would not be parallel to the separation between the masses, causing the system as a whole to spontaneously undergo torsional oscillations.…”
Section: Onboard Gravitational Experimentsmentioning
confidence: 93%
“…The external field entering this equation is the Newtonianequivalent quantity g N,ext , the Newtonian gravity exerted by the rest of our Galaxy on the Solar System. As discussed in section 9.3.1 of Banik & Zhao (2018d), the Sun's location in the outskirts of the Galactic disk means that it is quite accurate to use the spherically symmetric relation between g N,ext and the actual external field gext.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation